2019
DOI: 10.1109/access.2019.2913392
|View full text |Cite
|
Sign up to set email alerts
|

Analysis Method of the Capture Tolerance Capability for an Orthogonally Distributed Satellite Capture Device

Abstract: In this paper, an analysis method is proposed to determine capture tolerance capability of an orthogonal distributed satellite capture device that exhibits characteristics, including modularization, miniaturization, extensibility, and peripheral layout. The verifiable limit poses of the satellite are obtained when the pose error of the satellite reaches the boundary of the tolerance domain of the capture device. A dynamic model of a body combined with a satellite and robotic arm, and a contact dynamic model be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…5. The centroid and moment of inertia of the last link varies in the dynamic model of the combined body when compared with the dynamic model of the robotic arm [28]. The coordinate transformation of the robotic arm links is expressed as follows:…”
Section: ) Robotic Arm-container Combined Body Contact Dynamics Modelmentioning
confidence: 99%
“…5. The centroid and moment of inertia of the last link varies in the dynamic model of the combined body when compared with the dynamic model of the robotic arm [28]. The coordinate transformation of the robotic arm links is expressed as follows:…”
Section: ) Robotic Arm-container Combined Body Contact Dynamics Modelmentioning
confidence: 99%
“…Wang 1 based on the adaptive growth law of plant adventitious roots, the principle of mechanical stability of plant root growth was applied to the layout optimization of satellite bottom locking units, and the optimized results showed that the fundamental frequency of the system was significantly higher than that of the conventional results. Wang [2][3][4][5] put forward a kind of strategy based on adaptive sensing step by step, the posture error of space manipulator are analyzed, and get the space satellite capture lock release mechanism design basis, put forward the distribution of orthogonal satellite capture locking device tolerance ability analysis method, and puts forward a determine the orthogonal analysis method of distributed satellite capture devices capture is successful. Liu 6 analyzed the relationship between locking units and positions of different types of arms, determined the best locking point positions of different arms, and optimized the locking point positions of the space manipulator.…”
Section: Introductionmentioning
confidence: 99%
“…Rouleaut et al [7] implemented a redundant solution to maximize the operability of the robot and increase its functional workspace and developed a trajectory generation algorithm based on online vision to generate velocity commands to safely approach the target satellite and match its movement. Wang et al [8][9][10] proposed a step-by-step docking strategy based on adaptive sensing for an orthogonally distributed container docking device, then tested whether the capture was successful, and further determined a capture tolerance analysis method for the capture system. Ma et al [11] studied the optimal control problem associated with approaching and aligning one rigid body with another arbitrarily rotating rigid body and applied it to the satellite docking problem.…”
Section: Introductionmentioning
confidence: 99%